2008
DOI: 10.1111/j.1751-2980.2008.00329.x
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of hepatitis C virus infection in the largest province of Pakistan

Abstract: The study showed a high seroprevalence of anti-HCV antibodies in a general and apparently healthy population of the Punjab province of Pakistan. Drug injection, blood transfusion and needle stuck were the factors most strongly associated with HCV infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
67
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(76 citation statements)
references
References 24 publications
7
67
2
Order By: Relevance
“…This prevalence is lower than that of studies with populations of a similar age in Germany (0.7% and 0.8%) 34,35 , and in the United States (0.3%) 36 . It is also lower that that found in Northern Brazil in volunteers aged below 19 years old (2.1%) 14 and in Pakistan in volunteers aged between 6 and 15 (9.6%) 37 , and corroborates that found in Spain (0%) in a population aged below 19 38 . As foreseeable, due to the young age of participants, our results show a low risk of hepatitis C infection.…”
Section: Resultssupporting
confidence: 62%
“…This prevalence is lower than that of studies with populations of a similar age in Germany (0.7% and 0.8%) 34,35 , and in the United States (0.3%) 36 . It is also lower that that found in Northern Brazil in volunteers aged below 19 years old (2.1%) 14 and in Pakistan in volunteers aged between 6 and 15 (9.6%) 37 , and corroborates that found in Spain (0%) in a population aged below 19 38 . As foreseeable, due to the young age of participants, our results show a low risk of hepatitis C infection.…”
Section: Resultssupporting
confidence: 62%
“…The first finding is the identification of chronic HCV infection as a major risk factor for the development of HCC in Pakistan, because anti-HCV was observed in > 63% of patients with HCC. The overall anti-HCV prevalence rate is 14%-15% and HBV carrier rate is 2%-3% in the general population of Pakistan [29,40] . Overall, our data are consistent with the results of studies already reported from high-risk areas for HCC such as Japan, Italy and Spain, where majority of reported HCC cases are HCV-related [6][7][8] .…”
Section: Discussionmentioning
confidence: 99%
“…Qualitative and quantitative detection of HCV RNA HCV qualitative RT-PCR was carried out as described previously [29] . HCV RNA was quantified using a SmartCycler II Real-time PCR (Cepheid, USA), using HCV RNA quantitative kits (Sacace Biotechnologies, Italy) according to the kit protocol.…”
Section: Hbv Qualitative Polymerase Chain Reaction (Pcr)mentioning
confidence: 99%
“…A large number of patients, almost 26% got the infection because they were administered intravenous injections from the GP clinics, which were recognized for reusing the syringes [29]. People who got the injections were more likely to get HCV infection as compared to those who did not get the injections as shown in Table 3 [43].…”
Section: A Unnecessary Therapeutic Injections: Pakistan Wasmentioning
confidence: 87%
“…Several studies have shown that multiple and unnecessary use of injections, unsafe medical/ surgical procedures, use of contaminated razors by barbers, ear, nose piercing, blood transfusions and needle stick injuries (NSI) are major risk factors for HCV infection in Pakistan.29 Following Figure 3 shows the prevalence of HCV infection in Pakistan due to different risk factors ranging from 27% because of multiple use of needles to 2% due to needle stick injuries [29].…”
Section: Common Risk Factors For Hcv Transmission In Pakistanmentioning
confidence: 99%